2017
DOI: 10.1002/jcp.26049
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis biomarkers and their targeting ligands as potential targets for tumor angiogenesis

Abstract: Angiogenesis is known as one of the hallmarks in cancer which could play a key role in providing oxygen and nutrients for tumor cells. It has been shown that tumor cannot grow without sufficient development of new blood vessels. Accordingly, targeting angiogenesis, especially endothelial cells, could be considered as a common therapeutic target in tumors and more investigation on already existing biomarkers and potentially new biomarkers of endothelial cells seems to be necessary in cancer therapy. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 236 publications
0
110
0
Order By: Relevance
“…Solid tumors require persistent angiogenesis, which involves the formation of new vessels from pre-existing ones to allow for tumor cell growth and metastasis [29]. Without angiogenesis, cancer cell growth is restricted to a few millimeters and the cancer cells cannot escape into blood circulation to cause distant metastases [30].…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors require persistent angiogenesis, which involves the formation of new vessels from pre-existing ones to allow for tumor cell growth and metastasis [29]. Without angiogenesis, cancer cell growth is restricted to a few millimeters and the cancer cells cannot escape into blood circulation to cause distant metastases [30].…”
Section: Discussionmentioning
confidence: 99%
“…; Mashreghi et al . ). Increasing evidence has indicated that miRNAs are associated with the initiation and progression of several diseases such as cardiovascular disease, stroke, diabetes, and cancer (Mirzaei et al .…”
Section: Astrocytoma and Glioblastomamentioning
confidence: 97%
“…78 Many studies demonstrated cancer cell-derived exosomes play an important role in increasing angiogenesis. Therefore, its inhibition properties can be a noteworthy feature.…”
Section: The Role Of Exosomes In Angiogenesismentioning
confidence: 99%